Risk Factors Related to the Event of Anaemia in Pregnant Mothers - Tita Adilla Kaniasari; Faizah Betty Rahayuningsih (Indonesian Journal of Global Health Research, 2025)
Anaemia poses a significant health risk for pregnant women, increasing the likelihood of severe complications such as premature delivery, low birth weight, and maternal fatalities. This study investigates risk factors associated with anaemia in pregnancy using a case-control design with a quantitative approach. The participants included 200 medical records of pregnant women including 100 medical records of pregnant women who experienced anaemia during pregnancy and 100 medical records of pregnant women who did not experience anaemia, selected based on specific criteria, inclusion criteria in the study: Medical records of pregnant women at RSUD Dr. Moewardi Surakarta from 2023 to 2024, including maternal age, gestational age, parity, circumference of upper arm status, ANC visits, education level, employment status and haemoglobin values. Exclusion criteria in the study: Incomplete medical records of pregnant women. Secondary data from medical records were analysed using chi-square tests with a significance level of p<0.05. The findings revealed that gestational age (p=0.038), parity (p=0.028), and chronic energy deficiency status or CED (p=0.003) significantly influenced anaemia incidence. Conversely, maternal age (p=0.987), frequency of ANC visits (p=0.190), education level (p=0.537), and occupation (p=0.474) showed no significant associations. The study concludes that gestational age, parity, and CED status are key risk factors for anaemia in pregnancy, emphasizing the need for targeted health interventions to address these determinants and reduce anaemia prevalence.